Performance of desert black goat under extensive production systems in North Sinai in Egypt - Ahmed, A.M.; Kandil, M.H.; El-Shaer, H.M.; Metawi, H.R. (2001)
A production system approach was used to study the performance of desert black goat under semi-aird conditions in North Sinai. A random sample of 19 goat breeders was taken. Least squares analysis of variance was performed using fixed effects linear models for all productive traits to develop the technical coefficients used in the study. Biological criteria were kg of kids weaned per doe joined and kg of kids marketed per doe joined. Gross margin per head of goat and output/input ration were used as criteria of the economic efficiency of the existing production system. The technical coefficients for the studied area were 80.5%, 1.5, 11.0%, 12.2 and 15.9 for conception rate, twining rate, weaning mortality up to 4 months, kg of goat was LE 62.4 and output/input ratio was 1.85. These result indicated that with improvements in management, it is feasible to substantially improve the level of performance of goats.